Bridging local perceptions and co-creation for sustainable payment environmental services design: A framework for innovative forest financing - Febriant Isabella Yusuf (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Payment for Environmental Services (PES) has emerged as a crucial conservation instrument supporting climate change mitigation efforts in tropical regions. Although PES initiatives have been implemented in several parts of Indonesia, their distribution remains uneven, particularly in Eastern Indonesia such as Buton Island. Given the island’s distinctive topography, rich biodiversity, and the presence of the North Buton Wildlife Reserve, the region holds significant potential for developing PES schemes that address ongoing threats such as illegal logging and habitat degradation. Methods: This study explores local community perspectives in North Buton regarding future PES development, focusing on three interconnected dimensions: ecological, socio-economic, and cultural. Using a co-creation and knowledge-sharing framework to promote participatory policy design, data were collected over two months in three sub-districts North Kulisusu, West Kulisusu, and North Wakorumba through surveys with 227 respondents and complementary stakeholder interviews. Findings: Findings revealed that communities prioritised the preservation of spring ecosystems and the planting of multipurpose trees as future PES activities, while agricultural assistance was identified as the most preferred form of incentive. Although the local Kaago-ago ritual represents an important element of cultural identity, it does not directly align with PES objectives. Conclusion: These findings provide valuable input for formulating inclusive, bottom-up policies that integrate ecological resilience, socio-economic improvement, and cultural sensitivity in future PES initiatives across the North Buton Wildlife Reserve. Novelty/Originality of this article: This study presents a pioneering effort to design a bottom-up PES model specifically for Eastern Indonesia's unique biodiversity hotspots, a region often overlooked in environmental policy research.